Aggregated mesoporous nanoparticles for high surface area light scattering layer TiO(2) photoanodes in Dye-sensitized Solar Cells - Al-Attafi, Kadhim (Sci Rep, 2017)
Hierarchically structured aggregates, consisting of TiO(2) nanoparticles were produced via one-step solvothermal syntheses with a mixed solvent system containing both acetic acid and ethanol. Two of the resulting structures, one ~700 nm and the other ~300 nm in diameter, were found to be comprised of 8.5 nm and 10.5 nm anatase crystals, and possess specific surface areas of 138 and 106 m(2) g(−1) respectively. These particles were incorporated into Dye-sensitized Solar Cells (DSCs) as high surface area scattering layers, along with a layer of a transparent material. Solar-to-electric conversion efficiencies (PCE) of 9.1% and 8.2% were recorded using these aggregated particles as compared to those of commonly used large particles scattering layer 7.4%.